2010
DOI: 10.1088/0965-0393/18/4/045004
|View full text |Cite
|
Sign up to set email alerts
|

A geometric approach to modeling microstructurally small fatigue crack formation: II. Physically based modeling of microstructure-dependent slip localization and actuation of the crack nucleation mechanism in AA 7075-T651

Abstract: The objective of this paper is to develop further a framework for computationally modeling microstructurally small fatigue crack growth in AA 7075-T651 (Bozek et al 2008 Modelling Simul. Mater. Sci. 16 065007). The focus is on the nucleation event, when a crack extends from within a secondphase particle into a surrounding grain, since this has been observed to be an initiating mechanism for fatigue crack growth in this alloy. It is hypothesized that nucleation can be predicted by computing a non-local nucleati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(101 citation statements)
references
References 43 publications
2
99
0
Order By: Relevance
“…Fatigue indicator parameters (FIPs) were employed in [51] in fatigue studies on a peak-aged aluminium alloy in which fatigue crack nucleation is premised to be preceded by the development of persistent slip local to a non-shearable cracked particle inclusion. Fatigue cracks are thought to develop more rapidly in this material than in those for which PSBs do develop, and typically, in the experimental study, the regions of slip localisation were found to be quite diffuse.…”
Section: Nucleation Criteria and Microcracksmentioning
confidence: 99%
“…Fatigue indicator parameters (FIPs) were employed in [51] in fatigue studies on a peak-aged aluminium alloy in which fatigue crack nucleation is premised to be preceded by the development of persistent slip local to a non-shearable cracked particle inclusion. Fatigue cracks are thought to develop more rapidly in this material than in those for which PSBs do develop, and typically, in the experimental study, the regions of slip localisation were found to be quite diffuse.…”
Section: Nucleation Criteria and Microcracksmentioning
confidence: 99%
“…Similar to the studies of nickel-based alloys, detailed three-dimensional finite element models of aluminum 7075-T651 have been generated to predict the initiation of cracking at the microstructural scale (Hochhalter, 2010). To better understand the slip accumulation during cyclic loading that precedes nucleation events, these finite element models were generated using observed microstructural data that included the configuration and location of constituent particles and grain microstructural details.…”
Section: Modeling Near-crack-tip Plasticity At the Micro Scalementioning
confidence: 99%
“…By incorporating models for slip accumulation, a relationship between plastic exhaustion and crack growth can be computed 17 .…”
Section: Damage Accumulation In Aluminum Microstructuresmentioning
confidence: 99%
“…The discrepancy between simulations and experiments has attracted considerable attention among researchers because it prevents the reliable and accurate modeling of fracture in particular and puts doubt on the reliability of the atomistic simulations in general 17,31 . Most likely, the source of this discrepancy is related to the very different length (nanometers vs. millimeters) and time (nanoseconds vs. seconds) scales at which simulations and experiments are usually performed.…”
Section: Atomistic Simulation Of Crack Growthmentioning
confidence: 99%